An Overview of Response Surface Methodology Approach to Optimization of Hydrogen and Syngas Production by Catalytic Reforming of Greenhouse Gases (CH4 and CO2) - Ayodele, Bamidele V.; Sureena, Abdullah (INTECH, 2018)
Catalytic reforming of Methane (CH4) and carbon dioxide (CO2) is one of the techniques used for the production of hydrogen and syngas. This technique has dual advantages of mitigation of greenhouse gases and production of hydrogen and syngas which are often used as intermediates for the synthesis of valuable chemical products and oxygenates. This study presented an overview of the application of response surface methodology (RSM) in the optimization of hydrogen and syngas production from catalytic reforming of CH4 and CO2. The different catalytic system that has been employed together with the nature of experimental design, input parameters, responses, the optimum conditions and the maximum values of their responses were examined. The future research direction in the application of RSM to optimization of hydrogen and syngas production by catalytic reforming of CH4 and CO2 was recommended.